UPAYA PENINGKATAN KAPASITAS KESIAPSIAGAAN BENCANA GEMPA BUMI DAN TSUNAMI PADA KOMUNITAS SEKOLAH DI SMP NEGERI 13 PADANG - Shelvy Haria Roza; Melisa Yenti; Arinil Haq; Anggela Pradiva Putri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
Children are one of the most vulnerable groups at risk of being affected by disasters. The frequent occurrence of repeated earthquakes in the city of Padang has caused panic among students during lessons. This is because students are still weak in disaster preparedness. Efforts that can be made include improving earthquake and tsunami disaster preparedness in the school community through disaster preparedness education and training. SMP Negeri 13 Padang is one of the schools located in the earthquake and red tsunami zone, which already has a community of disaster smart students. However, they have never received disaster preparedness education and training. This activity aims to increase the capacity for earthquake and tsunami disaster preparedness in the school community. The method used is planning with program socialization; implementing activities to provide disaster preparedness education and emergency training through lectures, demonstrations, and simulations; providing disaster preparedness pocketbooks to the school environment; and evaluating by pretest and post-test of activity results. The activity results are the average increase in student knowledge, namely in the disaster-smart student community from 13.28 to 13.89, an increase in earthquake and tsunami disaster preparedness skills in the disaster-smart student community at SMP Negeri 13 Padang, and the availability of an alert pocketbook. Disaster. It is hoped that schools can provide and develop disaster preparedness education on an ongoing basis by including it in the school education curriculum.